1996
DOI: 10.1074/jbc.271.2.889
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Conserved Histidine Residues in Cephalosporium acremonium Isopenicillin N Synthase by Site-directed Mutagenesis

Abstract: The isopenicillin N synthase of Cephalosporium acremonium (cIPNS) involves a catalytically important non-heme iron which is coordinated credibly to histidine residues. A comparison of the IPNS genes from various microbial sources indicated that there are seven conserved histidine residues. These were individually replaced by leucine residues through site-directed mutagenesis, and the sites of mutation were confirmed by DNA sequencing. The seven mutant genes were cloned separately into the vector pET24d for exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…A role for histidines as putative iron ligands has recently been defined on the basis of the crystal structure of isopenicillin N synthase from Aspergillus nidulans [ 151 and by site-directed mutagenesis of the isopenicillin N synthase enzymes from Streptomyces jurnonjinensis and Cephalosporium acremorzium [16,171. Using the three-dimensional structure of isopenicillin N synthase, it was concluded that the manganese ion was attached by His214, His270, Asp216, and Gln330.…”
Section: Discussionmentioning
confidence: 99%
“…A role for histidines as putative iron ligands has recently been defined on the basis of the crystal structure of isopenicillin N synthase from Aspergillus nidulans [ 151 and by site-directed mutagenesis of the isopenicillin N synthase enzymes from Streptomyces jurnonjinensis and Cephalosporium acremorzium [16,171. Using the three-dimensional structure of isopenicillin N synthase, it was concluded that the manganese ion was attached by His214, His270, Asp216, and Gln330.…”
Section: Discussionmentioning
confidence: 99%
“…1) [ I , 21. This emerging class of enzymes now rivals heme enzymes in the diversity of oxidative transformations catalyzed.…”
mentioning
confidence: 99%
“…From the ~H-NMR spectra of cIPNS, three imidazole groups were thought to ligate to Fe2 § and Ming et al,(4) postulated an iron coordination model in which three histidines were required for the formation of isopenicillin N. However, site-directed mutagenesis investigations of cIPNS revealed the involvement of only two histidine residues, H216 and H272, by the loss of IPNS activity upon replacement of these histidines individually with leucine (1,5). The removal of the imidazole group of these histidine residues with the concomitant loss of activity indicated that these side groups are involved in catalysis.…”
Section: -(K-o-aminoadipyl)-l-cysteinyl-d-valinementioning
confidence: 99%
“…1) of penicillin and cephalosporin antibiotics. Alignment of the amino acid sequence of IPNS with other nonheme ferrous-requiring enzymes have shown that IPNS share three regions of relatively high sequence conservation (1). Since the involvement of conserved cysteine residues in iron binding has been discounted (2), histidine residues have been considered as potential ligands for iron binding (3).…”
Section: Introductionmentioning
confidence: 99%